Phase Transformation of Rice Husk Ash in the Synthesis of ZSM-5 without Organic Template - Didik Prasetyoko; Neneng Ayunanda; Hamzah Fansuri; Djoko Hartanto; Zainab Ramli (Journal of Mathematical and Fundamental Sciences, 2012)
Phase transformation of rice husk ash in the synthesis of ZSM-5 without organic template at various crystallization times has been studied. Zeolite has been synthesized using the hydrothermal method at 175 °C with molar ratio 10Na2O : 100SiO2 : 2Al2O3 : 1800H2O with addition of silicalite-1 as seed. Solids were characterized using X-ray diffraction (XRD), infrared (IR) spectroscopy and scanning electron microscopy (SEM) techniques. Analysis of the results of XRD and IR spectroscopy indicated that ZSM-5 crystalstarted to form at 12 h of crystallization time, reaching high crystallinity after 24 h. With a crystallization time of more than 48 h, the ZSM-5 crystals had completely transformed into more stable quartz phase. Results indicated that phase transformation has occurred, in which an amorphous phase of rice husk ash has been transformed to ZSM-5 crystal phase during the early crystallization stage and continued to transform to disordered Î±-cristobalite phase and lastly quartz phases. SEM showed that the morphology of the ZSM-5 crystal was of an irregular hexagonal shape with particle size distribution around 3-7 Î¼m.